Core slicing: closing the gap between leaky confidential VMs and bare-metal cloud - Zhou, Ziqiao; Shan, Yizhou; Cui, Weidong; Ge, Xinyang; Peinado, Marcus; Baumann, Andrew (17th USENIX Symposium on Operating Systems Design and Implementation, 2023)
Virtual machines are the basis of resource isolation in today's public clouds, yet the security risks of entrusting that isolation to a cloud provider's hypervisor are substantial. Such concerns have motivated the design of hardware extensions for "confidential VMs" that seek to remove the hypervisor from the trusted computing base by adding a highly-privileged firmware layer that checks hypervisor actions, and supports memory encryption and remote attestation. However, the hypervisor retains control of resource management and observes associated actions of the guest including nested page table faults and CPU scheduling, and thus confidential VMs remain vulnerable to an ever-changing variety of hypervisor-level side channel attacks. Bare-metal cloud servers avoid such leaks, but remain a niche due to the high cost of dedicated hardware. We observe that typical cloud VMs run with a static allocation of memory and discrete cores, and increasingly rely on I/O offload, thus negating the apparent need for a hypervisor and the fragile hypervisor/guest isolation boundary. Our design, core slicing, enables multiple untrusted guest OSes to run on shared bare-metal hardware. To ensure isolation without the complexity of virtualization, we propose simple hardware extensions that restrict guests to a static slice of a machine's cores, memory and virtual I/O devices, and delegate resource allocation to a dedicated management slice. We demonstrate practicality and evaluate performance with prototypes for RISC-V and x86.